Toward a more accurate estimate of the prevalence of hepatitis C in the United States. Issue 5 (25th August 2015) - Edlin, Brian R.; Eckhardt, Benjamin J.; Shu, Marla A.; Holmberg, Scott D.; Swan, Tracy
<x xml:space="preserve">Abstract</x> Data from the 2003‐2010 National Health and Nutrition Examination Survey (NHANES) indicate that about 3.6 million people in the United States have antibodies to the hepatitis C virus, of whom 2.7 million are currently infected. NHANES, however, excludes several high‐risk populations from its sampling frame, including people who are incarcerated, homeless, or hospitalized; nursing home residents; active‐duty military personnel; and people living on Indian reservations. We undertook a systematic review of peer‐reviewed literature and sought out unpublished presentations and data to estimate the prevalence of hepatitis C in these excluded populations and in turn improve the estimate of the number of people with hepatitis C in the United States. The available data do not support a precise result, but we estimated that 1.0 million (range 0.4 million‐1.8 million) persons excluded from the NHANES sampling frame have hepatitis C virus antibody, including 500, 000 incarcerated people, 220, 000 homeless people, 120, 000 people living on Indian reservations, and 75, 000 people in hospitals. Most are men. An estimated 0.8 million (range 0.3 million‐1.5 million) are currently infected. Several additional sources of underestimation, including nonresponse bias and the underrepresentation of other groups at increased risk of hepatitis C that are not excluded from the NHANES sampling frame, were not addressed in this study. Conclusion: The number of US residents who have been infected with hepatitis C is unknown but is probably at least 4.6 million (range 3.4 million‐6.0 million), and of these, at least 3.5 million (range 2.5 million‐4.7 million) are currently infected; additional sources of potential underestimation suggest that the true prevalence could well be higher. (Hepatology 2015;62:1353–1363)